Crying Wolf: Concluding that Wolves were not Restored - Mech, L. David (DigitalCommons@University of Nebraska - Lincoln, 2008)
In 2007, the USA removed (delisted) the grey wolf (Canis lupus) in the upper Midwest from the Endangered Species List. After 35 years of being considered endangered, these wolves had increased from 750 in 38 400 km2 of Minnesota (Fuller et al. 1992) to over 4100 inhabiting 110 000 km2 of Minnesota, Wisconsin, and Michigan. Conservationists celebrated this event as a most significant success. Suddenly, however, this milestone was challenged by Leonard & Wayne (2007) based on preliminary genetic findings that wolves of the upper Midwest 100 years ago were different from 69 per cent of the current population. There are, however, both technical and logical problems with this challenge.